Pengaruh Gender Diversity Dan Board Independence Terhadap Emisi Karbon Dengan Media Exposure Sebagai Moderasi - Rahmat Febrianto; Monica Verginia; Amy Fontanella (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2022)
Global warming is becoming a problem faced now. Global warming can affect climate change. One of the causes of climate change in the world is GHG caused by human activities. The international public's efforts to respond to climate change events began when the UNFCCC was signed. The purpose of this study is to analyze the effect of gender diversity and board independence on the disclosure of carbon emissions with media exposure as moderation in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2020. Sampling in this study is purposive sampling technique and became 135 companies. Regression analysis shows that the interaction of board independence on media exposure affects the disclosure of carbon emissions. Meanwhile, gender diversity, board independence and interaction of gender diversity on media exposure have no effect on the disclosure of carbon emissions.